Characteristic of Midwife’s who Refer Complex Obstetrics Cases: Karakteristik Bidan yang Merujuk kasus Kebidanan Komplek - Arietta R.D. Pusponegoro; Astrid M. P. Iskandar (Indonesian Socety of Obstetrics and Gynecology, 2020)
Abstract Objective: To identify reasons for referring and characteristics of midwives who practice independently and its relation with complicated cases referred to RSCM.Method: Descriptive analytic case-control. Medical records of patients referred directly to RSCM in January 2016-July 2017 were obtained, then information about midwives and obstetric cases, along with its complications, were collected. Interview and analysis of six characteristics of midwives were conducted. Characteristics analyzed were age, education, training, duration of practice, number of patients ever treated, also distance and travel time of the referral process.Results: All midwives refer due to inadequate facilities. There is a statistically significant correlation between duration of practice and number of patients, with the complicated cases referred directly to RSCM, with OR 7.036 and 6.032, respectively.Conclusion: Midwives refer due to inadequate facilities, and so patients can be treated immediately. Characteristics that affect midwives to refer complicated cases: duration of practice and number of patients. It is necessary to re-evaluate the position of midwives who practiced independently in BPJS, refresher programs, and monitoring by relevant agencies. Further research is needed with more samples and combining midwives' and patients' characteristics in referral cases. Confounding and external factors are identified first in order to do a thorough analysis.Keywords: complicated cases, midwives' characteristics, midwives who practiced independently, referral, referral system. Abstrak Tujuan: Mengetahui alasan rujuk dan karakteristik bidan yang berpraktik mandiri serta hubungannya dengan kasus komplikatif yang dirujuk ke RSCM.Metode: Deskriptif analitik kasus kontrol. Data diambil dari rekam medis pasien yang dirujuk langsung ke RSCM di bulan Januari 2016 hingga Juli 2017, kemudian informasi mengenai data bidan dan kasus obstetri beserta komplikasinya dikumpulkan. Dilakukan wawancara dan analisis enam karakteristik bidan. Karakteristik yang dianalisis yaitu usia, pendidikan, pelatihan, lama waktu berpraktik, jumlah pasien yang pernah ditangani, serta jarak dan waktu tempuh proses merujuk. Hasil: Keseluruhan bidan merujuk karena fasilitas yang tidak memadai. Terdapat hubungan yang bermakna antara waktu praktik dan jumlah pasien yang pernah ditangani, dengan kasus komplikatif yang dirujuk langsung ke RSCM, dengan nilai OR 7.036 dan 6.032.Kesimpulan: Bidan merujuk karena fasilitas tidak memadai dan agar pasien langsung ditangani. Karakteristik bidan yang mempengaruhi dalam merujuk yaitu lama waktu praktik dan jumlah pasien yang ditangani. Perlu dilakukan evaluasi ulang mengenai kedudukan bidan yang berpraktik mandiri di BPJS, program penyegaran bidan, serta monitoring oleh instansi terkait. Perlu penelitian lanjut dengan sampel lebih banyak serta menggabungkan karakteristik bidan dan pasien pada kasus-kasus rujukan. Faktor perancu dan eksternal diidentifikasi terlebih dahulu agar analisis dilakukan menyeluruh.Kata kunci: bidan yang berpraktik mandiri, karakteristik bidan, kasus komplikatif rujukan, sistem rujukan